Studi pengelolaan sampah terpadu skala kawasan Desa Ciangsana, Kecamatan Gunung Putri, Kabupaten Bogor - Ratnaningsih Ruhiyat; Iveline Anne Marie; Djohar Tjintamani; Emelia Sari; Hartini Hartini; Dewi Nilamsari; Juliana Josephina Alexsandra; Siska Herliana; Isnaeni Nabilah; Gusni Muharam; Yudha Melianto (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
The crisis regarding the final waste disposal site (TPA) in various regencies and cities is caused by the waste management that still relies on the collection and transport system and disposes of it to the TPA. The 3R (Reduce, Reuse, Recycle) Waste Processing Site (TPS) plays an important role in waste management on a regional scale. TPS 3R makes it easier to handle waste, because does not require a large area and it closer from the houses to waste collection. This study aims to analyze the potential waste utilization in Ciangsana Village as an effort to reduce waste and support national policies on waste management. The study was conducted through a survey of waste source mapping, waste generation, characteristics and composition. Furthermore, data analysis is carried out to select the appropriate processing technique. The results showed that the composition of waste in Ciangsana Village consisted of 50.3% food waste, 15.4% plastic, 8.5% paper/box wood, 2.3% cloth, rubber and leather, 1.3% metal and glass and 17.5% residual. The TPST-3R which is equipped with waste processing into RDF and BSF in Ciangsana is expected to reduce the waste that is disposed of in the TPA by 70-80%.